Conflict about quitting predicts the decision to stop smoking gradually or abruptly: evidence from stop smoking clinics in Malaysia - Wee, L.H.; Shahab, L.; Bulgiba, A.; West, R. (2011)
Background: Little is known about the extent to which smokers attending stop-smoking clinics experience conflicting motivations about their quit attempt, whether such conflict can be understood in terms of a single dimension and if this 'conflict about quitting' differs from motivation to stop smoking and is associated with a smoker's choice of method to stop smoking (stopping gradually or abruptly). Method: Sociodemographic, smoking and quit attempt characteristics as well as measures relating to conflict about stopping smoking were recorded in a cross-sectional survey of 198 smokers attending five quit smoking clinics in Malaysia. Results: Five measures (having seriously thought about quitting before, being happy about becoming a non-smoker, being strongly motivated to stop, intending to stop smoking completely and believing in stopping for good this time) were loaded onto a single factor that could be labelled 'conflict about quitting'. The resultant scale had moderate internal reliability (Cronbach's alpha = .625). Most smokers exhibited conflicting motivations about stopping smoking, with over half (52.0, 95 CI 45.1-59.1) scoring 2 or higher on the 5-point conflict scale. 'Conflict about quitting' was significantly associated with the decision to stop smoking gradually rather than abruptly controlling for other variables (OR 1.36, 95 CI 1.05-1.76) and was more strongly associated with the choice of smoking cessation method than motivation to stop smoking. Conclusions: 'Conflict about quitting' can be conceptualised as a single dimension and is prevalent among smokers voluntarily attending stop-smoking clinics. The finding that smokers who display greater conflict about quitting are more likely to choose gradual cessation may explain contradictory findings in the literature regarding the effectiveness of different methods of smoking cessation.